Rezadeiras e rezadores das almas: um estudo sobre a vivência das religiosidades no sertão de Princesa - Melo, José Anchieta Bezerra de (2021)
This thesis presents a reading of the country people’s devotion to the Almas Vaqueiras and to the Thirteen Blessed, Wise and Aware Souls. The research adopted as theme of study men and women, healers of Souls, and their religious experiences in relation to this devotion. The field of analysis was the Hinterland of Princesa, a region bordering the states of Paraíba and Pernambuco, where this devotion occurs. The objective was to understand how the healers experiences are articulated with the devotion to the Holy Souls. For this, we sought to know how these healers associate daily life with devotion practices; to identify the mechanisms that enable dialogue and proximity to the Holy Souls; to understand the process of transmitting traditional knowledge in the devotees' community. We also sought to understand how the effectiveness of prayers is present in the speeches of the healers and a blessed person. Ethnography and Oral History were used as methodological guidance. In the study, it was observed that devotion to souls has a Catholic reference, is based on a relationship of commitment, wrapped in mystery and wonder, and obeys a principle of exchange. Religious experiences enable healers to have a closer relationship with the sacred. Such a condition gives the healer a special status based on the gift, the credibility he acquires with blessed people and the proximity to the community. Healers exercise their power through the domain of privileged knowledge, using strategies of secrecy and precautions with strong prayers and healing. The research pointed out that the experience of the gift is the means by which healers transcend the individualism. In this way, they work in a field of mediation using prayer and the experience of devotion to the Holy Souls. Finally, it was observed that this devotion constitutes a rich possibility of understanding religiosities from the aspect of relations with the sacred, represented by the Holy Souls, and mediated, occasionally, by magical practices and rites.